Presence of genes encoding enterotoxins in Staphylococcus aureus isolates recovered from food, food establishment surfaces and cases of foodborne diseases - Machado, Virginia (2020)
The aim of this study was to describe the microbiological characteristics and profile of genes encoding enterotoxins in 95 Staphylococcus aureus isolates obtained between April 2011 and December 2014 from foodstuffs, persons and surfaces of retail food stores. After microbiological identification and antimicrobial susceptibility testing, polymerase chain reactions (PCR) were performed, targeting sea, seb, sec, sed and see genes that code for classical enterotoxins (ET) A-E, and three additional genes: seg, seh and sei, coding for so-called “new enterotoxins” G, H and I. The isolates were characterized by Pulsed Field Gel Electrophoresis (PFGE), and five selected isolates were further analyzed through Multi Locus Sequence Typing (MLST). It is noteworthy that 54.7% of the examined isolates harbored one or more of the investigated ET gene types. Most positive isolates carried more than one ET gene up to five types; seg was the most frequent ET gene, followed by sei. Five enterotoxin-coding isolates also coded for some antimicrobial resistance genes. Two of them, and four additional non-enterotoxic isolates carried erm genes expressing inducible clindamycin resistance. PFGE-types were numerous and diverse, even among enterotoxin-coding strains, because most isolates did not belong to known foodborne outbreaks and the sampling period was long. MLST profiles were also varied, and a new ST 3840 was described within this species. ST 88 and ST 72 enterotoxin-coding isolates have been identified in other regions in association with foodborne outbreaks. This manuscript reports the first systematic investigation of enterotoxin genes in S. aureus isolates obtained from foodstuffs and infected people in Uruguay